History of islam (the age of the rightly-guided caliphs) al-khulafa ar-rashiddun Abu Bakr as-Siddiq (R.A) - Aziz abdul maulvi (Lahore Darussalam, 2024)
"History of Islam: Abu Bakr as-Siddiq (RA)" is the first volume in the History of Islam series by Darussalam. Written by Maulvi Abdul Aziz, this book presents a detailed, authentic, and engaging account of the life and caliphate of Abu Bakr as-Siddiq (RA), the first Caliph of Islam. Designed especially for Muslim youth, the book provides a rich historical perspective on the early days of Islam, highlighting the leadership, wisdom, and devotion of Abu Bakr (RA) in preserving and spreading the message of Islam after the passing of Prophet Muhammad (PBUH). The narrative is supported by colorful illustrations, maps, and real-time pictures of historical places, making the reading experience both educational and visually engaging.